2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition 2018
DOI: 10.1109/cvpr.2018.00240
|View full text |Cite
|
Sign up to set email alerts
|

Social GAN: Socially Acceptable Trajectories with Generative Adversarial Networks

Abstract: Understanding human motion behavior is critical for autonomous moving platforms (like self-driving cars and social robots) if they are to navigate human-centric environments. This is challenging because human motion is inherently multimodal: given a history of human motion paths, there are many socially plausible ways that people could move in the future. We tackle this problem by combining tools from sequence prediction and generative adversarial networks: a recurrent sequence-to-sequence model observes motio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
2,096
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,803 publications
(2,115 citation statements)
references
References 49 publications
14
2,096
0
5
Order By: Relevance
“…Encoder-decoder architectures excel in many sequential problems like trajectory prediction [1], [2]. Encoder-decoder architectures consist of two separate recurrent networks: the encoder processes the input sequence x i = (x i,1 , .…”
Section: Encoder-decodermentioning
confidence: 99%
See 2 more Smart Citations
“…Encoder-decoder architectures excel in many sequential problems like trajectory prediction [1], [2]. Encoder-decoder architectures consist of two separate recurrent networks: the encoder processes the input sequence x i = (x i,1 , .…”
Section: Encoder-decodermentioning
confidence: 99%
“…A multitude of models have been proposed for the problem of predicting trajectories, mainly concerning pedestrians [2], [1]. We employ the encoder-decoder model from Section III-C for this task, using the Stanford Drone Dataset (SDD) [22].…”
Section: Trajectory Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…If Gaussian noise were used as auxiliary input, an array of Gaussian noise was feed-forwarded together with an MRI slice in the training process as follows: 10 different sets of Gaussian noise were first generated and only the "best" set (i.e., the set that yielded the lowest M * loss (Equation 1)) was used to update the DEP model's parameters. Note that this approach is similar to and inspired by Min-of-N loss in 3D object reconstruction (Fan et al, 2017) and variety loss in Social GAN (Gupta et al, 2018). In the testing process, 10 different sets of Gaussian noise were generated and the average performance was calculated.…”
Section: Experiments Setupmentioning
confidence: 99%
“…It is shown that the proposed neural network was capable of reproducing more realistic flow in multiple scenarios. Besides, other newly developed deep learning method, such as generative adversarial network (GAN) [12,13], also has begun applying on pedestrian trajectory prediction. However, the pedestrian movement modeling researches based on artificial neural network are still insufficient and are necessary to make further studies.…”
Section: Introductionmentioning
confidence: 99%